COMPRESSIVE STRENGTH AND SPLITING-TENSILE STRENGTH OF GEOPOLYMER CONCRETE USING VARIATION IN MAXIMUM SIZE OF COARSE AGGREGATE - Noor Arif Inderawan; Yulin Patrisia (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2017)
The purpose of this research is to study the mechanical behavior of geopolymer concrete using the variation in maximum size of coarse aggregate in the term of compressive strength and splitting-tensile strength. This study used variation on maximum size of course aggregate namely 10 mm, 20 mm and 30 mm. Fly ash is from AsamAsam Steam Electricity Power Plant, Indonesia. Cylindrical test specimen (size 100 mm x 200 mm) with number of test specimens counted 10 pieces for each variant of maximum size of aggregate coarse. The mixture of geopolymer concrete in this experiment contain fly ash of 400 kg/m3 with alkaline activator is Sodium Hydroxide (NaOH) with molarity of 10 M and Sodium Silicate (Na2SiO3). The ratio of Na2SiO3 to NaOH is 2:1 and the ratio of alkaline activator to fly ash is 0.4. Tests conducted for compressive strength test and tensile strength at age 14 and 21 day. The result shows that the smaller the maximum size of coarse aggregate, the greater compressive strength and splitting-tensile strength. Compressive strength and splitting-tensile strength for specimen with 10 mm, 20 mm, and 30 mm maximum size of aggregate are 11.04 MPa and 6.12 MPa, 10.82 MPa and 5.22 MP, 10.06 MPa and 4.84 MPa respectively.